The three faces of competitization: From marketization to a multiplicity of competition - Carina Altreiter; Claudius Gräbner-Radkowitsch; Stephan Pühringer; Ana Rogojanu; Georg Wolfmayr (Johannes Kepler University Linz, Research Project SPACE - Spatial Competition and Economic Policies, 2023)
The article is a contribution to the evolving field of competition research. More precisely our paper provides a comprehensive typology of the different ways competitization is and has been studied across different disciplines and research programs. The article goes beyond a classical literature review as it provides a systematic integration of a broad debate. Based on differences regarding analytical scope, ontology and normative connotations, we delineate three distinct ideal types or 'faces' of competitization and discuss some theoretical positions and empirical examples for each ideal type of competitization. As we show in the concluding part of the article, the typology offers a useful framework for categorizing key elements of competitization and exploring their interdependencies. Additionally, the framework offered in this article shows which forms of critique towards competitization are inherent to different approaches and where we find blind spots that can be illuminated by an integrated approach towards competitization.
Keywords: 330; capitalism; competition; economic sociology; interdisciplinarity; political economy; neoliberalism